Anophthalmia and microphthalmia in children: associated ocular, somatic and genetic morbidities and quality of life. (4th March 2022) - Fahnehjelm, Cecilia; Dafgård Kopp, Eva; Wincent, Josephine; Güven, Evin; Nilsson, Mattias; Olsson, Monica; Teär Fahnehjelm, Kristina
ABSTRACT: Purpose: To report ocular outcome, somatic co-morbidities, genetics, and quality of life in children born with anophthalmia (A) or microphthalmia (M). Methods: Thirty-five children (19 boys) with A/M underwent ophthalmological examinations and a review of medical records. Parents of 12/22 cases completed the Pediatric Quality of Life Inventory (PedsQL). Results: Age at examination ranged from 7 months to 18 years (median 2.3 years). Ten cases were totally blind or had light perception. Isolated A/M occurred in 16/35 cases, while somatic, psychomotor, neuroradiological and/or genetic pathology occurred in 19/35 cases both in the bilateral (7/9) and in the unilateral group (12/26). Among 26 unilateral cases, 4/16 with one normal eye had associated problems compared to 9/10 if the contralateral eye was pathological ( p < .01). There was an increased risk for heart defects in children with psychomotor delay ( p = .04). Pathogenic genetic abnormalities were identified in 10/24 cases. Neuroimaging demonstrated pathology in 14/20 cases with corpus callosum dysgenesis (6/20) being the most common. The median total PedsQL score of parent reports for ages 2–12 was 52.4 (range 22.6–100). Conclusions: Somatic, psychomotor and/or neuroradiological pathologies were more common in bila-teral than unilateral cases, but the difference was not significant. There was decreased risk in unilateral cases with one normal eye. Genetic defects occurred in both unilateral and bilateral cases. Health-related quality of life was reduced.